A novel highly sensitive imprinted polymer-based optical sensor for the detection of Pb(II) in water samples - Meza López, Flor de Liss; Khan, Sabir [UNESP]; Picasso, Gino; Sotomayor, Maria Del Pilar Taboada [UNESP] (Elsevier, 2021)
This paper reports the successful development and application of a novel ion highly efficient imprinted polymer-based optical sensor toward Pb2+ determination. The sensor, which was highly selective for Pb2+, was synthesized with rhodizonate – a highly selective ligand for Pb2+. The polymeric materials, which were synthesized directly onto a quartz optical fiber of 1 mm diameter and 4.2 cm long, were adapted to a bundle of optical fibers for the conduct of reflectance measurements. The polymerized fibers, which acted as sensing phase of the optical sensor, were characterized by Fourier transform infrared (FTIR) spectroscopy, scanning electronic microscopy (SEM), and attenuated total reflectance (ATR). The response profile of the optical sensors was optimized, and the parameters, such as pH and interaction time, were defined. The following data were obtained under the optimized conditions employed: linear response range of 10 to 100 μg L−1; linear regression coefficient of R2 = 0.9973; detection limit of 85 ng L−1; and sensitivity of 0.1412 nm ppb−1. The results obtained from reproducibility and repeatability studies showed RSD values below 4%. Through the study of selectivity, the following selectivity factor values for Pb2​​+ with respect to Cu2+, Ni2+, Cd2+, Zn2+, Co2+ and Fe2+were obtained: 43.90, 13.25, 15.09, 9.73, 12.07 and 9.90, respectively. The studies carried out on the proposed sensor demonstrated the feasibility of its implementation and application in samples of environmental interest with recovery percentages of almost 100%. Thus, based on the findings obtained in this study, the sensor was found to be highly sensitive and selective for the detection and quantification of Pb2+ in real water samples.
Keywords: Ion-imprinted polymer; Lead ion; Optical sensor; Rhodizonate; Sensitive detection